Augmented analysis for yield performance and agronomic characteristics of upland rice lines grown under coconut plantation - Angelita Puji Lestari; Aris Hairmansis; Rini Hermanasari; Yullianida Yullianida; Suwarno Suwarno (Jurnal Ilmu Pertanian, 2022)
Establishment of shade-tolerant rice varieties aims to utilize the dry land under tree stands. A field experiment on rice yield under coconut plantation was conducted at farmer field in Calincing Tegalbuleud Sukabumi, West Java, Indonesia. The experiment involved 307 upland promising lines, 42 of which were selected in comparison to four check varieties, namely Jatiluhur, Batutugi, Limboto and Situpatenggang. The experiment was conducted according to augmented design with four replications. The analysis of variance indicated significant difference in yield per ha between blocks and no significant differences in days to flowering, plant height and number of productive tiller between blocks. Meanwhile, significant differences were observed in plant height and number of productive tillers between all check varieties. Under shade of coconut plantation, some lines could perform better and had higher performance than check varieties. Four lines ofB11957SR* 232182SI2MR2PN21, B12743MR18232PN1111, B13498D9, and B12743MR18235PN1031 had significantly higher yield compared to the check variety with the highest yield, which is Limboto. The utperforming lines can be proposed as promising rice lines for shading tolerance. However, most of the lines were proved to be underperforming for yield and its components in prevailing conditions.